Simulation and automatization of measurements process in laser interferometry - Morozov, N.V. (Functional Materials, 2005)
Mathematical simulation of mechanical vibration amplitude measuring processes by laser interferometry has been considered. A software has been developed to obtain the time dependence of the interferometer output signal at various parameters of vibration and of the measuring unit and to automatize amplitude determination. Рассмотрено математическое моделирование процесса измерений амплитуд механических колебаний с помощью лазерной интерферометрии. Разработана программа, которая позволяет получить зависимости значения выходного сигнала интерферометра от времени при различных значениях параметров колебаний и измерительной установки, а также автоматизировать процесс определения амплитуды. Розглянуто математичне моделювання процесів вимірювання амплітуд механічних коливань у лазерній интерферометры. Розроблено програму, що дозволяє отримати залежність величини сигналу з виходу інтерферометра від часу для різних параметрів коливань і вимірювальної установки, а також автоматизувати процес визначення амплітуди.